2022
DOI: 10.1002/ajh.26579
|View full text |Cite
|
Sign up to set email alerts
|

EBV‐positive diffuse large B‐cell lymphoma, not otherwise specified: 2022 update on diagnosis, risk‐stratification, and management

Abstract: Disease Overview Epstein Barr virus‐positive (EBV+) diffuse large B‐cell lymphoma (DLBCL), not otherwise specified (NOS) is an entity included in the WHO classification of lymphoid neoplasms since 2016. EBV+ DLBCL, NOS, is an aggressive B‐cell lymphoma associated with EBV infection, and a poor prognosis with standard chemotherapeutic approaches. Diagnosis The diagnosis is made through a careful pathological evaluation. Detection of EBV‐encoded RNA (EBER) is considered standard for diagnosis; however, a clear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 193 publications
3
35
0
1
Order By: Relevance
“…EBV-positive diffuse large B-cell lymphoma (DLBCL), which was formerly designated as EBV-positive DLBCL of the elderly, usually occurs in individuals aged >50 years, with an inferior clinical prognosis in comparison to EBV-negative DLBCL [ 146 ]. The incidence of EBV-positive DLBCL is less than 5% in Western countries, but that percentage goes up to 10–15% in Asian and Latin American countries [ 147 ]. Most EBV-positive DLBCL cases have an activated B-cell (ABC) phenotype, expressing MUM1/IRF4, and are negative for CD10 and BCL6 [ 147 ].…”
Section: Ebv-associated Malignancesmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV-positive diffuse large B-cell lymphoma (DLBCL), which was formerly designated as EBV-positive DLBCL of the elderly, usually occurs in individuals aged >50 years, with an inferior clinical prognosis in comparison to EBV-negative DLBCL [ 146 ]. The incidence of EBV-positive DLBCL is less than 5% in Western countries, but that percentage goes up to 10–15% in Asian and Latin American countries [ 147 ]. Most EBV-positive DLBCL cases have an activated B-cell (ABC) phenotype, expressing MUM1/IRF4, and are negative for CD10 and BCL6 [ 147 ].…”
Section: Ebv-associated Malignancesmentioning
confidence: 99%
“…The incidence of EBV-positive DLBCL is less than 5% in Western countries, but that percentage goes up to 10–15% in Asian and Latin American countries [ 147 ]. Most EBV-positive DLBCL cases have an activated B-cell (ABC) phenotype, expressing MUM1/IRF4, and are negative for CD10 and BCL6 [ 147 ]. Expression of NF-κB and phosphorylated STAT3 are more commonly seen in EBV-positive DLBCL compared with EBV-negative DLBCL [ 146 ].…”
Section: Ebv-associated Malignancesmentioning
confidence: 99%
“…EBV-positive DLBCL was included in the 2016 World Health Organization (WHO) classification of lymphoid neoplasms. In the era of chemoimmunotherapy, EBV-positive DLBCL is an aggressive B-cell lymphoma with a worse prognosis than EBV-negative DLBCL, even if several studies showed similar outcomes for both forms [ 90 ].…”
Section: Ebv-associated Malignanciesmentioning
confidence: 99%
“…Este tipo de linfoma asociado a la infección por VEB es raro, y se caracteriza por una alta tasa de replicación de células grandes con núcleos vesiculares, con un tamaño del doble de los linfocitos normales [29]. Se considera que aproximadamente el 9 % de los linfomas difusos de células B grandes son positivos para VEB [30], pero también se ha asociado con factores de riesgo como la radiación ionizante, la inmunosupresión y algunos químicos como pesticidas, entre otros [1]. En un metaanálisis reciente en 2021, Hwang y colaboradores [31] encontraron una positividad general del 7,9 % de linfoma difuso de células B grandes asociado a VEB, con una frecuencia del 9,2 % en Asia y América del Sur, y de 4,7 % en las poblaciones occidentales.…”
Section: Linfoma B Difuso De Células Grandesunclassified